Pesantren Modern Ta’din Al-Syakirin Medan: Sejarah dan Kontribusi dalam Dunia Pendidikan - Nasution, Abdul Ghani Jamora; Sari, Ardila; Zahratunnisa, Elvira; Alwi, Fachrizal; Pasaribu, Fitri Yanti; Lilis, Lilis (Peneliti.net, 2023)
The Ta'dib Al-Syakirin Modern Islamic Boarding School in Medan has contributed to the world of education. This Islamic boarding school is an Islamic educational institution that has a holistic educational approach, including religious, academic and character development aspects. In this article, the background of Islamic boarding schools, their history and founding, as well as the vision and mission of Islamic boarding school education are explained in detail. Apart from that, this article discusses the Islamic boarding school curriculum, focusing on developing educational character, increasing academic achievement, and the impact produced by this Islamic boarding school in society. In developing character education, this Islamic boarding school plays an important role in forming students who have strong religious, ethical and moral values. This article also explains Islamic boarding schools' efforts to improve student academic achievement through effective learning approaches and supporting programs. Overall, this article provides a comprehensive overview of the contribution of the Ta'dib Al-Syakirin Medan Modern Islamic Boarding School to the world of education. This article also provides suggestions that can help Islamic boarding schools face challenges and take advantage of opportunities to continue to develop. This research has important relevance in the context of educational development in Indonesia, especially in understanding the role and potential of Islamic boarding schools in forming a quality young generation.